Genome-wide identification and characterization of microRNA genes and their targets in flax (Linum usitatissimum) - Barvkar, Vitthal T.; Pardeshi, Varsha C.; Kale, Sandip M.; Qiu, Shuqing; Rollins, Meaghen; Datla, Raju; Gupta, Vidya S.; Kadoo, Narendra Y. (Planta, 2013)
MicroRNAs (miRNAs) are small (20-24 nucleotide long) endogenous regulatory RNAs that play important roles in plant growth and development. They regulate gene expression at the post-transcriptional level by translational repression or target degradation and gene silencing. In this study, we identified 116 conserved miRNAs belonging to 23 families from the flax (Linum usitatissimum L.) genome using a computational approach. The precursor miRNAs varied in length; while most of the mature miRNAs were 21 nucleotide long, intergenic and showed conserved signatures of RNA polymerase II transcripts in their upstream regions. Promoter region analysis of the flax miRNA genes indicated prevalence of MYB transcription factor binding sites. Four miRNA gene clusters containing members of three phylogenetic groups were identified. Further, 142 target genes were predicted for these miRNAs and most of these represent transcriptional regulators. The miRNA encoding genes were expressed in diverse tissues as determined by digital expression analysis as well as real-time PCR. The expression of fourteen miRNAs and nine target genes was independently validated using the quantitative reverse transcription PCR (qRT-PCR). This study suggests that a large number of conserved plant miRNAs are also found in flax and these may play important roles in growth and development of flax.
Keywords: Digital expression analysis; Gene cluster; Linseed; miRNA; MiRNA target transcript; Promoter analysis

Genome-wide identification and characterization of nucleotide binding site leucine-rich repeat genes in linseed reveal distinct patterns of gene structure - Kale, Sandip M.; Pardeshi, Varsha C.; Barvkar, Vitthal T.; Gupta, Vidya S.; Kadoo, Narendra Y. (Genome, 2013)
Plants employ different disease-resistance genes to detect pathogens and to induce defense responses. The largest class of these genes encodes proteins with nucleotide binding site (NBS) and leucine-rich repeat (LRR) domains. To identify the putative NBS-LRR encoding genes from linseed, we analyzed the recently published linseed genome sequence and identified 147 NBS-LRR genes. The NBS domain was used for phylogeny construction and these genes were classified into two well-known families, non-TIR (CNL) and TIR related (TNL), and formed eight clades in the neighbor-joining bootstrap tree. Eight different gene structures were observed among these genes. An unusual domain arrangement was observed in the TNL family members, predominantly in the TNL-5 clade members belonging to class D. About 12% of the genes observed were linseed specific. The study indicated that the linseed genes probably have an ancient origin with few progenitor genes. Quantitative expression analysis of five genes showed inducible expression. The in silico expression evidence was obtained for a few of these genes, and the expression was not correlated with the presence of any particular regulatory element or with unusual domain arrangement in those genes. This study will help in understanding the evolution of these genes, the development of disease resistant varieties, and the mechanism of disease resistance in linseed.
Keywords: Flax; in silico gene expression; motif analysis; NBS-LRR; Phylogenetic analysis; Promoter analysis